Stress-dependent incipient plasticity of a face-centered-cubic-based Al0.3CoCrFeNi multi-principal element alloy with nano-scaled phase separation. (October 2021) - Zhang, L.J.; Yu, P.F.; Zhang, C.Z.; Fan, J.T.; Li, G.
Abstract: The stress-dependent incipient plasticity was probed by measuring the first pop-in behavior in a face-centered-cubic-based Al0.3 CoCrFeNi multi-principal element alloy with nano-scaled phase separation. A large number of indentation measurements revealed that the operation of a bimodal distribution for the maximum shear stress was associated with different dislocation nucleation sites. This bimodal distribution phenomenon can be used to characterize the structural heterogeneity of the alloy. The activation volume and the dislocation nucleation rate were calculated to make a further investigation to the different dislocation nucleation mechanisms. Graphical abstract: Image, graphical abstract